Stability of Embankments on Soft Ground Lessons from Failures - Kim Huat, Bujang (Universiti Putra Malaysia Press, 1995)
A number of embankments founded on soft clays have become unstable during construction of a major highway project in Malaysia. Three of the embankments were back analysed based on their geometries before the failure. Measured in situ vane shear strengths were used in total stress analyses to determine the factor of safety at failure. Performances of the soft clay foundation with regards to vertical and horizontal displacements, and piezometric response, when the failure was imminent were also described.